Comparative protein profiling of serum and plasma using an antibody suspension bead array approach. - Schwenk, J; Igel, U; Kato, B; Nicholson, G; Karpe, F; Uhlén, M; Nilsson, P (2010)
In the pursuit towards a systematic analysis of human diseases, array-based approaches within antibody proteomics offer high-throughput strategies to discover protein biomarkers in serum and plasma. To investigate the influence of sample preparation on such discovery attempts, we report on a systematic effort to compare serum and plasma protein profiles determined with an antibody suspension bead array. The intensity levels were used to define protein profiles and no significant differences between serum and plasma were observed for 79% of the 174 antibodies (targeting 156 proteins). By excluding 36 antibodies giving rise to differential intensity levels, cluster analysis revealed donor-specific rather than preparation-dependent grouping. With a cohort from a clinically relevant medical condition, the metabolic syndrome, the influence of the sample type on a multiplexed biomarker discovery approach was further investigated. Independent comparisons of protein profiles in serum and plasma revealed an antibody targeting ADAMTSL-4, a protein that would qualify to be studied further in association with the condition. In general, the preparation type had an impact on the results of the applied antibody suspension bead array, and while the technical variability was equal, plasma offered a greater biological variability and allowed to give rise to more discoveries than serum.